Isomalt attenuates hepatic steatosis in rats via modulating gut microbiota and its metabolic function - Zhandong Yang; Huihui Su; Xueqing Chen; Ziyan Ni; Heqing Tao; Yonghong Jiang; Liang Peng (Journal of Functional Foods, 2024)
Growing studies have shown the preventive effects of isomalt against metabolic diseases, nevertheless, its efficacy and action mechanisms on nonalcoholic fatty liver disease (NAFLD) remain unknown. Herein, isomalt supplementation significantly attenuated the high-sucrose diet-induced hepatic steatosis. Mechanically, dietary isomalt restored hepatic de novo lipogenesis dysfunction and intestinal epithelial integrity. Moreover, isomalt consumption regulated gut microbiota composition, including improving abundance of probiotic Akkermansia, but suppressing pathogens Acinetobacter and Corynebacterium_1. Quantification analyses of short-chain fatty acids showed that isomalt reduced faecal acetate concentrations, whereas elevated propionate and butyrate in hepatic steatosis. Additionally, targeted metabolomics profiling of tryptophan metabolism showed that isomalt increased faecal levels of 5-hydroxytryptophan, indole-3-carboxaldehyde and kynurenic acid, but reduced concentrations of 5-hydroxyindoleacetic acid and xanthurenic acid in rats. Thereby, our data demonstrate that dietary isomalt attenuates hepatic steatosis possibly via modulation of gut microbiota and its metabolic function, which provides new insights into preventing and treating NAFLD in future.